Impact of Biomass Source and Pyrolysis Parameters on Physicochemical Properties of Biochar Manufactured for Innovative Applications - Uroić Štefanko, Ana; Leszczynska, Danuta (Frontiers in Energy Research, 2020)
Manufacturing biochar for energy and high-tech applications requires a specific set of physicochemical parameters based on relationships between initial pyrolytic conditions and properties of starting material, namely biomass. This study compares 20 types of biochar produced from five diverse waste biomasses at two pyrolytic temperatures (400, 700°C), processing times (2, 5 h) and heating rates (26, 5°C/min). The manufactured biochar was tested for the yield, fixed C, ash load, size of developed surface area, porosity, nutrients, and minerals. Leachate tests were performed to determine the stability of biochar, their pH, conductivity, and presence of dissolved nutrients and metals. The proximate analysis demonstrated an increase in fixed C linked to temperature increase from 400 to 700°C. Biochar produced from organic-rich biomass such as corn stover showed higher content of nutrients, especially potassium and phosphorus on their surfaces and in their leachates, which influenced the development of its surface area at 700°C. The increase of temperature with prolonged residence time has generated more stable and mostly aromatic structures within biochar when compared to other studied conditions. These findings were confirmed by the FTIR spectra that indicated amplified condensation of aromatic and aliphatic carbons (C = C, C = O, C-H) and a decrease of phenolic bonded water (-OH bonded). Consequently, a specific application of biochar should ultimately dictate the choice of optimal pyrolytic conditions linked to the components of initial biomass.